Pengembangan Ontologi Semantik Pada Domain Upacara Manusa Yadnya - Pratama, I Komang Widia; Julia Budiantari, Ni Made; Eka Suryaningsih, Ni Luh; Pramartha, Cokorda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 3 (2025): JELIKU Volume 13 No 3, February 2025DO - 10.24843/JLK.2025.v13.i03.p12, 2025)
This research focuses on the development of an ontology that represents the elements involved in Manusa Yadnya, one of the ceremonies in Balinese Hindu tradition. Using the Methontology approach, a structured method for ontology design, the study developed a semantic model encompassing key components such as ceremonies, participants, ritual offerings, execution times, and locations. The ontology was implemented using Protégé software, allowing for graphical design, property definition, and integration of data from Balinese cultural literature. Evaluation of the ontology was conducted using SPARQL queries to verify its consistency and accuracy in answering questions related to the domain. The results demonstrated the ontology's effectiveness in organizing and retrieving information systematically, making it a valuable tool for cultural preservation. This ontology serves as a foundation for the development of broader knowledge-based systems and is expected to be integrated into web or mobile applications for easier access by the public.